THEORETICAL AND METHODOLOGICAL FUNDAMENTALS STUDY OF THE HUMANITIES IN HIGHER T TECHNICAL EDUCATIONAL INSTITUTION (Pedagogy of Higher and Secondary Education, 2008)
The article is devoted to forming problem of integrated knowledge for humanitarian students' disciplines of technical universities. Grounded, that a system of integrated knowledge from humanitarian disciplines expediently inculcate into sparring process of technical universities in appearance of sparring metaobjects, which contains the different components. Developed the maintenance selection criterions of humanitarian metaobjects for technical universities.
Keywords: higher education; knowledge; fundamental training; expert analysis; module-structured content of sparring discipline